Intercalation stage dependence of core electronic excitations in Li-intercalated graphite from inelastic X-ray scattering - Stutz, Guillermo Eduardo (2017)
Fil: Stutz, Guillermo Eduardo. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía, Física y Computación; Argentina.